BACH'S DIRECTIVES IN MADELINE MILLER'S THE SONG OF ACHILLES - Kamelang, Ikral; Sugaryamah, Deuis; Ardiansyah, Erlan Aditya (PARADIGM: Journal of Language and Literary Studies, 2024)
The nature of directive speech acts is to make someone do something. The hearer responds to the speaker's utterances by carrying out particular actions. This study aims to find directive speech acts from written dialogue in a novel and then examine the types of directive speech acts. The object of this study was Madeline Miller's The Song of Achilles. The data for this study was analyzed using Bach's theory of categories of directive speech acts. This study employed a qualitative approach with a content analysis design. The results of this study showed that the characters from The Song of Achilles used all types of directive speech acts. Of the 293 data found in the novel, the most frequently used speech act was questions which had 93 data (31.7%). Meanwhile, the least used speech act was permissives with a total of 20 data (6.8%).